Bilateral renal artery stenosis in pediatric patient with Post-Streptococcal Glomerulonephritis in children: A case report - Nieken Susanti; Irma Nur Sukmawati (Universitas Muhammadiyah Surabaya, 2024)
The immune-complex mediated inflammation known as post-streptococcal glomerulonephritis (PSGN) was once thought to be one of the most common causes of acute nephritis in children. In this case, we present a 12-year-old girl experiencing symptoms of cough phlegm, congested breath, change of urine color, decreased urine production, as well swelling in the area face and legs after experiencing fever, pain swallowing, cough, and runny nose 3 weeks before admission. On physical examination, the pressure blood was 130/80 mmHg. In addition, the palpebral and extremity were edema bilateral, hyperemia of the tonsil and pharynx, enlarged tonsils T2/T3, and detritus were found. Laboratory and Imaging Tests: hematology; leukocytes 12,930, albumin 2.4 g/dl, on urinalysis, obtained urine cloudy, brownish, leukocyturia, hematuria, and proteinuria, there was also an increase in ASTO titers, abdominal ultrasound found bilateral renal artery stenosis and nephritis bilateral acute. The patient in this case presented with bilateral renal artery stenosis, which is a rare finding in PSGN cases. Management of PSGN include bed rest, low salt diet, fluid balance, as well supportive treatment with IVFD D5 ½ NS 15 drops/min (micro), Antibiotics injection of Ceftriaxone 1 gram/12 hours on the first day and continued with oral Erythromycin 4x500mg, injection prednisolone 3x1, injection Furosemide 1x1 amp, oral spironolactone and sublingual nifedipine, and hypoalbuminemia correction. Prognosis in patients with the given GNAPS governance optimally will give good results.